Cobalamin and Thiamine Effect on Microalgae Biomass Production in the Glagah Consortium - Setyaningrum, Tri Wahyu; Budiman, Arief; Suyono, Eko Agus (Journal of Tropical Biodiversity and Biotechnology, 2023)
The Glagah consortium is a mixed culture of various microalgae and bacteria isolated from Glagah Beach, Yogyakarta. Cobalamin and thiamine, which are given by symbiotic bacteria, are assumed will increase biomass. This study aimed to determine the effect of cobalamin and thiamine on microalgae biomass production in the Glagah consortium. The microalgae of Glagah consortium were cultivated for 10 days with vancomycin and gentamicin antibiotic as treatment and without antibiotics as a control. The parameters measured included the number of bacterial colonies, cobalamin and thiamine levels measured by LC-MS, chlorophyll a and b levels, cell density of microalgae and dry biomass. The highest level of cobalamin and thiamine was in the Glagah consortium without antibiotics. Cobalamin and thiamine increased in the exponential phase along with the increasing Staphylococcus sp. colonies. The Quantity of Staphylococcus sp. colonies in the exponential phase was 62.105 (cfu/mL). The level of cobalamin in the exponential phase was 2.33 µg/L and the level of thiamine in the exponential phase was 49.71 µg/L. The highest productivity dried weight biomass was 0.0134 g/L/day in the day-6th on the Glagah consortium without antibiotics. This result showed that microalgae and bacterial interaction was mutualism symbiosis involving cobalamin and thiamine that increased in the exponential phase along with the increasing Staphylococcus sp. colonies. This interaction was able to increase biomass microalgae.